VIOLENT CRIMES AND ADVERSE CHILDHOOD EXPERIENCES IN YOUNG OFFENDERS AT BLITAR JUVENILE DETENTION CENTRE - Wilona, Jessica Shirleen; Rahayu, Yusti Probowati; Ayuni, Ayuni (Faculty of Psychology, Diponegoro University, 2020)
Violent crimes yield to fear and unsafe feelings have been also done by children. The General Strain theory explained that violence was occurred due to the criminal coping of individuals, who experienced the situation of pressures that yield into anger which might be developed into violent behaviour. Adverse Childhood Experiences (ACE) is a form of pressure within the family that might contribute to criminal coping. This research was aimed at investigating the differences of ACE on violent crimes and non-violent crimes. Participants of this study were 58 out of 213 boy offenders aged 12-18 years old in the Juvenile Detention Center in Blitar. These participants were chosen by the accidental sampling method based on the type of cases, in which 28 boys were on violent crimes (robbery, child protection, murder, and beating), while 30 boys were on non-violent crimes (theft and drug abuses). The measurement used was the ACE scale, applied with some modifications. The reliability coefficient of the ACE scale was .843. Data were analysed using a non-parametric method, which was the Mann-Whitney U. The examination of mean rank and the effect size of this study showed that ACE was higher on violent crimes, even though this result was not supported by the hypothesis examination result, which was not significant (U = 3.47, p = .129). It could be concluded that ACE on the violent crimes group tended to be higher compared to the non-violent crimes group.